WDR74 induces nuclear β-catenin accumulation and activates Wnt-responsive genes to promote lung cancer growth and metastasis. (28th February 2020) - Li, Yumei; Chen, Fan; Shen, Weiyu; Li, Bifei; Xiang, Rong; Qu, Lijuan; Zhang, Chen; Li, Gao; Xie, Huanzhang; Katanaev, Vladimir L.; Jia, Lee
Abstract: Lung cancer has been notorious for its lack of advance in clinical therapy, urging for effective therapeutic targets. WD repeat-containing protein 74 (WDR74) has previously been implicated in tumorigenesis, but its mechanistic functions remain not well understood. Herein, WDR74 expression was observed to be increased upon lung cancer progression from healthy normal tissues to the primary cancer and further to the metastatic cancer. Through gain- and loss-of-function approaches, we found that WDR74 regulated lung cancer cell proliferation, cell cycle progression, chemoresistance and cell aggressiveness in vitro . Moreover, a xenograft mouse model disclosed that WDR74 knockout inhibited lung cancer growth and metastasis, whereas WDR74 overexpression reciprocally enhanced these characteristics. Mechanistically, WDR74 promoted nuclear β-catenin accumulation and drove downstream Wnt-responsive genes, thus revealing that WDR74 activated the Wnt/β-catenin signaling pathway. Collectively, WDR74 inducing nuclear β-catenin accumulation and driving the downstream Wnt-responsive genes expression facilitates lung cancer growth and metastasis. WDR74 can serve as a candidate target for the prevention and treatment of lung cancer in clinic. Highlights: WDR74 is identified as a leading gene contributing to lung cancer progression. WDR74 controls cell proliferation, chemoresistance, cell aggressiveness to promote lung cancer growth and metastasis. WDR74 induces nuclear β-catenin accumulation and drives Wnt-responsive genes. WDR74 emerges as a candidate target for clinical lung cancer prevention and treatment.